To complete the table using the function \( y = x^2 + 1 \), we can calculate the y-values for each x-value provided.
Calculations:
-
For \( x = -2 \): \[ y = (-2)^2 + 1 = 4 + 1 = 5 \]
-
For \( x = -1 \): \[ y = (-1)^2 + 1 = 1 + 1 = 2 \]
-
For \( x = 0 \): \[ y = (0)^2 + 1 = 0 + 1 = 1 \]
-
For \( x = 1 \): \[ y = (1)^2 + 1 = 1 + 1 = 2 \]
-
For \( x = 2 \): \[ y = (2)^2 + 1 = 4 + 1 = 5 \]
Now we can summarize the completed table:
| x | y | |-----|-----| | -2 | 5 | | -1 | 2 | | 0 | 1 | | 1 | 2 | | 2 | 5 |